Can the effect of tall structures on birds be isolated from other aspects of development?. (22nd January 2014) - Walters, Kimberly; Kosciuch, Karl; Jones, Jason
ABSTRACT As technology and energy development increase, undeveloped land and land traditionally used for agriculture now host structures not part of the historical landscape. These structures (e.g., communication towers, transmission lines) are taller than many objects in natural landscapes. Concerns have been raised regarding the effects of tall structures on birds, primarily functional habitat loss due to avoidance. Two hypotheses have been advanced to explain observed patterns of birds near tall structures: increased perceived predation risk and neophobia. We examined the literature (1969–2013) and used a vote‐counting methodology to document 1) the reported direction (positive or negative) of a potential tall‐structure effect, 2) whether the effect of tall structures can be isolated from other effects of development, 3) whether the study design lent itself to drawing a supportable conclusion, and 4) whether the authors suggested a causal mechanism for any observed pattern. We did not detect any consistent response to tall structures, nor did we find evidence to support the two hypotheses. In addition, a structure's "tallness" could not be isolated from other factors associated with development such as human activity. Understanding causal mechanisms is important for management and conservation because observed effects might not be related to the tallness of the structure but to other factors that could be managed, such as timing of construction. Our results suggest that the effect of tall structures on birds is not well understood, and focused studies that examine before‐and‐after effects and specific causal mechanisms are needed to support effective project siting and conservation planning. © 2014 The Wildlife Society.